Questionnaire design administration protocol and sampling bias in education surveys - Valdez, Elisa Magno (2006)
In this research, three aspects of questionnaire design were studied--length of instrument, type of questions, and sequence of items. Administration protocol, another important variable in the study, included questionnaire administration, conveyance of importance of target respondent's participation, offer of reciprocation, and endorsement by an institution. Two universities in Metro Manila were chosen as venues of the educational surveys conducted to a total of 18 groups upon which the varied questionnaire designs and administration protocol were utilized--nine for each school. The study recommended the utilization of said mix of questionnaire design and administration protocol to reduce sampling bias and to ensure valid educational survey results.